Progression of diabetic retinopathy in patient with Graves’ disease - Urban, Beata; Bakunowicz-Łazarczyk, Alina; Peczyńska, Jadwiga (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The authors present the case of 16-year old girl with diabetes mellitus type 1. She had progression of diabetic retinopathy because of occurrence of Graves' disease. Surgical intervention (strumectomy subtotal, bilateral), was performed and regression of retinal changes was observed.